Analysis of energy consumption in coconut oil production with bromelin enzyme extract - Hamdhani Nino; Lily Yulinar; Rusdianasari Rusdianasari; Arizal Aswan; Irawan Rusnadi (Jurnal Teknik Kimia, 2023)
Indonesia has been facing the problem of domestic cooking oil since the beginning of 2022. This issue certainly does not reduce the number of people's consumption of cooking oil which causes the amount of energy consumption in the production process will also increasing. This study aims to obtain coconut oil in accordance with SNI 3741:2013, determine the effect of temperature and processing time as well as determine the amount of energy consumption in the coconut oil production process. One of the efficient ways to make coconut oil is by using the heating process method. This method will produce coconut oil that lasts longer because it has a lower water content. This study uses temperature variables with variations of 60 ᵒC, 65 ᵒC, 70 ᵒC, 75 ᵒC and 80 ᵒC and heating time with variations of 90 minutes, 120 minutes and 150 minutes. Based on the research that has been done, it can be concluded that the best treatment is at temperature variation of 70 ᵒC and heating time of 150 minutes which produces 355 ml of coconut oil with a fragrant smell of coconut oil and a clear golden yellow color with the water content of 0.0015 %, the free fatty acid content of 2.8205 %, the specific energy consumption (SEC) is 0.0066 and the required electricity cost is Rp.2.675,31. The coconut oil produced also complies with SNI 3741:2013 with the highest water content of 0.0024 % and the highest free fatty acid content of 3.3009 %. Specific Energy Consumption (SEC) values during the study ranged from 0.0038 to 0.0070 kWh/ml.